A Systematic Review of Amenable Resilience Factors That Moderate and/or Mediate the Relationship Between Childhood Adversity and Mental Health in Young People - Fritz, Jessica; de Graaff, Anne M.; Caisley, Helen; van Harmelen, Anne-Laura; Wilkinson, Paul O. (Frontiers in Psychiatry, 2018)
Background: Up to half of Western children and adolescents experience at least one type of childhood adversity. Individuals with a history of childhood adversity have an increased risk of psychopathology. Resilience enhancing factors reduce the risk of psychopathology following childhood adversity. A comprehensive overview of empirically supported resilience factors is critically important for interventions aimed to increase resilience in young people. Moreover, such an overview may aid the development of novel resilience theories. Therefore, we conducted the first systematic review of social, emotional, cognitive and/ or behavioural resilience factors after childhood adversity. Methods: We systematically searched Web of Science, PsycINFO and Scopus (e.g. including MEDLINE) for English, Dutch and German literature. We included cohort studies that examined whether a resilience factor was a moderator and/ or a mediator for the relationship between childhood adversity and psychopathology in young people (mean age 13-24). Therefore, studies were included if the resilience factor was assessed prior to psychopathology, and childhood adversity was assessed no later than the resilience factor. Study data extraction was based on the STROBE report and study quality was assessed with an adapted version of Downs and Black’s scale. The preregistered protocol can be found at: http://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42016051978. Results: The search identified 1969 studies, of which 22 were included (eight nationalities, study sample n range: 59-6780). We found empirical support for 13 of 25 individual-level (e.g. high self-esteem, low rumination), six of 12 family-level (e.g. high family cohesion, high parental involvement), and one of five community-level resilience factors (i.e. high social support), to benefit mental health in young people exposed to childhood adversity. Single versus multiple resilience factor models supported the notion that resilience factors should not be studied in isolation, and that interrelations between resilience factors should be taken into account when predicting psychopathology after childhood adversity. Conclusions: Interventions that improve individual, family, and/ or social support resilience factors may reduce the risk of psychopathology following childhood adversity. Future research should scrutinize whether resilience factors function as a complex interrelated system that benefits mental health resilience after childhood adversity.